The FHD/εppsilon Epoch of Reionisation power spectrum pipeline. (2019) - Barry, N.; Beardsley, A. P.; Byrne, R.; Hazelton, B.; Morales, M. F.; Pober, J. C.; Sullivan, I.
Abstract: Epoch of Reionisation (EoR) data analysis requires unprecedented levels of accuracy in radio interferometer pipelines. We have developed an imaging power spectrum analysis to meet these requirements and generate robust 21 cm EoR measurements. In this work, we build a signal path framework to mathematically describe each step in the analysis, from data reduction in the Fast Holographic Deconvolution (FHD) package to power spectrum generation in the ε ppsilon package. In particular, we focus on the distinguishing characteristics of FHD/ ε ppsilon: highly accurate spectral calibration, extensive data verification products, and end-to-end error propagation. We present our key data analysis products in detail to facilitate understanding of the prominent systematics in image-based power spectrum analyses. As a verification to our analysis, we also highlight a full-pipeline analysis simulation to demonstrate signal preservation and lack of signal loss. This careful treatment ensures that the FHD/ ε ppsilon power spectrum pipeline can reduce radio interferometric data to produce credible 21 cm EoR measurements.